A NOTE ON CHEEGER SETS - Figalli, Alessio; Maggi, Francesco; Pratelli, Aldo (Proceedings of the American Mathematical Society, 2009)
Starting from the quantitative isoperimetric inequality, we prove a sharp quantitative version of the Cheeger inequality.